2021
DOI: 10.1136/bmjopen-2020-046336
|View full text |Cite
|
Sign up to set email alerts
|

Sick leave and return to work for patients with anxiety and depression: a longitudinal study of trajectories before, during and after work-focused treatment

Abstract: ObjectivesSick leave due to anxiety and depression is a heterogeneous process constituting a pressing public health issue. This longitudinal study aimed to identify sick leave trajectories among patients before, during and after work-focused treatment, in all 29.5 months. We then aimed to determine the background and clinical characteristics of these trajectory groups.MethodsBackground and clinical data were collected by patient self-report (N=619) in an observational study in a specialised mental healthcare c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
3
2
1
Order By: Relevance
“…If resilience aids adjustment, it is presumed that the higher the resilience, the more likely the patient is to continue working. In fact, there are reports that the higher the resilience after receiving work‐focused treatment, the lower the risk of sick leave 28 . However, in the present study, there was no difference in initial resilience capacity and the course of employment (continued work group vs. leaving work group).…”
Section: Discussioncontrasting
confidence: 76%
“…If resilience aids adjustment, it is presumed that the higher the resilience, the more likely the patient is to continue working. In fact, there are reports that the higher the resilience after receiving work‐focused treatment, the lower the risk of sick leave 28 . However, in the present study, there was no difference in initial resilience capacity and the course of employment (continued work group vs. leaving work group).…”
Section: Discussioncontrasting
confidence: 76%
“…Patients are referred by their general practitioners for treatment of depression and anxiety. Patients at the clinic are generally of working age, and previous research has shown that on average, half the patients are on sick leave due to depression or anxiety at baseline [ 22 ]. They are then screened by a clinical psychologist using anamnestic information, the Beck Depression Inventory-II (BDI-II), the Beck Anxiety Inventory (BAI), and the MINI-International Neuropsychiatric Interview [ 23 – 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data [22]. They are then screened by a clinical psychologist using anamnestic information, the Beck Depression Inventory-II (BDI-II), the Beck Anxiety Inventory (BAI), and the MINI-International Neuropsychiatric Interview [23][24][25].…”
Section: Study Contextmentioning
confidence: 99%
“…Furthermore, different types of work interventions such as individual placement and support have been found useful to aid RTW for people suffering from more severe mental health illness and in need of more supported employment [35,36]. Patients that RTW later could also be struggling with other unresolved issues either at work or at home [37][38][39].…”
Section: Discussionmentioning
confidence: 99%